2016
DOI: 10.1039/c6tc00639f
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic control over intra- and intermolecular charge transfer can turn on the fluorescence emission of non-emissive coumarin

Abstract: Conjugated molecules bearing carbonyl groups typically exhibit weak fluorescence emission due to the presence of a non-radiative n-p* transition state. Strong fluorescence emission from n-p* chromophores has been sought through the use of synthetic approaches that incorporate strong electron donors, such as amines, into the conjugated structures. As an alternative to these existing approaches, we investigated two charge-transfer strategies using a series of 1-benzopyran-2-one (coumarin) derivatives. The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 101 publications
1
24
0
Order By: Relevance
“…In an attempt to develop highly fluorescent n –π* fluorophores, we recently performed an investigation into the aryl derivatives of 1-benzopyran-2-one (coumarin), a prototypical n –π* platform . Our study revealed that coumarin-based n –π* molecules become highly fluorescent upon the activation of charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to develop highly fluorescent n –π* fluorophores, we recently performed an investigation into the aryl derivatives of 1-benzopyran-2-one (coumarin), a prototypical n –π* platform . Our study revealed that coumarin-based n –π* molecules become highly fluorescent upon the activation of charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“… f Radiative lifetime: τ rad = τ F /Φ F g Radiative rate constant: k r = Φ F /τ F h Non-radiative rate constant: k nr = (1 – Φ F )/τ F …”
Section: Resultsmentioning
confidence: 99%
“…f Radiative lifetime: τ rad = τ F /Φ F 22. g Radiative rate constant: k r = Φ F /τ F 85. h Non-radiative rate constant: k nr = (1 − Φ F )/τ F 85.…”
mentioning
confidence: 99%
“…Two types of TADF emitters, donor‐acceptor type intramolecular charge transfer (CT) emitters, and intermolecular CT emitters, that have separate donor and acceptor molecules, are under development. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%